PENGARUH KEADILAN ORGANISASIONAL TERHADAP KINERJA PEGAWAI KANTOR KELURAHAN DI KECAMATAN PONOROGO KABUPATEN PONOROGO - Lestriana Reswandary; Herning Suryo Sardjono; Suwardi Suwardi (Master of Public Administration, Universitas Slamet Riyadi, 2023)
The purpose of this study is to describe the effect of distributive justice,procedural justice and interactional justice on employee performance. This typeof research is survey and classified in explanatory research. This research wasconducted in all Kelurahan Office in Ponorogo District,Ponorogo Regency. Thepopulation of this research is the employees of the Kelurahan Office in Ponorogodistrict, Ponorogo Regency, amounting to 187 employees. The research samplewas 94 people with proportional cluster random sampling technique. Datacollection techniques used questionnaires and literature studies. The data analysistechnique used multiple linear regression. The results showed that distributivejustice had a positive and significant effect on employee performance).Procedural justice has a positive and significant effect on employee performance.Interactional justice has a positive and significant effect on employeeperformance). Distributive justice, procedural justice and interactional justicehave a simultaneous effect on employee performance).Keywords: distributive justice, procedural justice, interactional justice,employee performance